Liquid Crystals: Liquid Crystal‐Induced Myoblast Alignment (Adv. Healthcare Mater. 3/2019). Issue 3 (7th February 2019) - Martella, Daniele; Pattelli, Lorenzo; Matassini, Camilla; Ridi, Francesca; Bonini, Massimo; Paoli, Paolo; Baglioni, Piero; Wiersma, Diederik S.; Parmeggiani, Camilla
Abstract : Polarized optical microscope image of C2C12 cells cultured on a liquid crystal (LC)‐based scaffold. The same image is recorded without and with a red, yellow, or green filter. In article1801489, Camilla Parmeggiani and co‐workers, LC‐based scaffolds are able to reflect the molecular organization inside the polymer in a unidirectional alignment of the global cell culture.